Faktor-Faktor yang Mempengaruhi Loyalitas Pelanggan: - Salsabela Eka Pancarini; Ambar Lukitaningsih; Agus Dwi Cahya (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
This research aims to test whether service quality, customer satisfaction, and brand image affect customer loyalty to Shopee users in the DIY area. This research took samples from several e-commerce users who were in the DIY area. The method of determining the sample is non-probability sampling using a purposive sampling method. Data collection was carried out using a questionnaire distributed using a google form. The number of questionnaires processed was 100 questionnaires obtained from the Hair formula, namely the indicator multiplied by 5. The research data were analyzed using multiple regression analysis and this processing was carried out using the SPSS version 26 application. The results of this study indicate that all independent variables simultaneously affect the dependent variable. But partially, Service Quality has no effect on Customer Loyalty, Customer Satisfaction has an effect on Customer Loyalty, and Brand Image has an effect on Customer Loyalty. Keywords: Service Quality; Customer Satisfaction; Brand Image; Service Loyalty